2013
DOI: 10.1016/j.cmet.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Obesity and Gut Microbiota Composition in Response to High-Fat, High-Sucrose Diet in Mice

Abstract: SUMMARY Obesity is a highly heritable disease driven by complex interactions between genetic and environmental factors. Human genome-wide association studies (GWAS) have identified a number of loci contributing to obesity; however, a major limitation of these studies is the inability to assess environmental interactions common to obesity. Using a systems genetics approach, we measured obesity traits, global gene expression, and gut microbiota composition in response to a high-fat/high-sucrose (HF/HS) diet of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
426
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 486 publications
(465 citation statements)
references
References 68 publications
(99 reference statements)
30
426
1
1
Order By: Relevance
“…In addition to prioritizing candidate genes, studies of natural variation in gene expression in mice should be useful in elucidating mechanisms relating to the gene-by-gene, gene-by-environment, and gene-by-sex interactions. 51,52,89 For example, although it is clear that genetic background contributes to weight gain and related traits in response to dietary challenge, 90 the inability to accurately ascertain environmental factors over a lifetime in humans has made molecular dissection difficult. In contrast, studies of natural variation in mice have revealed that gene-by-environment interactions can contribute substantially to the overall variance in traits such as obesity and that the underlying genes and pathways can be identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to prioritizing candidate genes, studies of natural variation in gene expression in mice should be useful in elucidating mechanisms relating to the gene-by-gene, gene-by-environment, and gene-by-sex interactions. 51,52,89 For example, although it is clear that genetic background contributes to weight gain and related traits in response to dietary challenge, 90 the inability to accurately ascertain environmental factors over a lifetime in humans has made molecular dissection difficult. In contrast, studies of natural variation in mice have revealed that gene-by-environment interactions can contribute substantially to the overall variance in traits such as obesity and that the underlying genes and pathways can be identified.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of natural variation in mice have revealed that gene-by-environment interactions can contribute substantially to the overall variance in traits such as obesity and that the underlying genes and pathways can be identified. 51,52 Whereas numerous studies have successfully mapped cis associations, few studies have reported trans-eQTLs because of small effect sizes, multiple testing thresholds, and computational burden. 22,37,91 These issues are consistent with the low reciprocal replication rates of trans-eQTLs identified in MuTHER and METSIM cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body fat percentage and body weight were tracked as described previously (14). The animal protocols for the study were approved by the Institutional Care and Use Committee (IACUC) at the UCLA and the City of Hope.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this study was to describe the sex difference in hepatic steatosis in a population of diverse inbred strains of mice known as the Hybrid Mouse Diversity Panel (HMDP) fed a high-fat high-sucrose (HF/HS) diet (22). The use of the HMDP provided a rich genetic background to assess both the phenotypes and genetic interactions associated with hepatic TG concentration in mice of both sexes.…”
Section: Accession Numbersmentioning
confidence: 99%